Hidden female smokers in Asia: a comparison of self-reported with cotinine-verified smoking prevalence rates in representative national data from an Asian population. Issue 6 (4th October 2011) - Jung-Choi, Kyung-Hee; Khang, Young-Ho; Cho, Hong-Jun
Abstract : Background: The low smoking prevalence in Asian women may be due to under-reporting. We therefore investigated gender difference in self-reported and cotinine-verified smoking prevalence rates in Korea Methods: We analysed data from 5455 individuals (2387 men and 3068 women) in the 2008 Korean National Health and Nutrition Examination Survey. A urniary cotinine concentration of 50 ng/ml was the cut-off distinguishing smokers from non-smokers. Sensitivity analysis was done using different cut-offs of 25, 75 and 100 ng/ml. Results: Cotinine-verified smoking rates were 50.0% for men and 13.9% for women, or 5.3% point and 8.0% point higher in absoulte terms, respectively, than the self-reported rates for men and women. Ratios of cotinine-verified to self-reported smoking rates were 2.36 for women and 1.12 for men. Of the 1620 cotinine-verified smokers, 12.1% of men and 58.9% of women classified themselves as non-smokers. Women who live with a spouse or parents tend to under-report their smoking more than those who live alone or with others. Conclusion: Since the number of self-reported female smokers was less than half of cotinine-verified smokers, current anti-smoking policies based on self-reported smoking prevalence rates in Korea should be further directed towards hidden female smokers. Also, biochemical verification needs to be considered with national tobacco surveys in Asian countries.